Eritrea : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
The paper presents statistical data on gross domestic product by sector, agricultural production, regional structure of the agricultural sector, food grain position, annual catch and sales of fish, and gross value of public enterprise production of Eritrea. It also includes data on Assab refinery production, purchases and sales by Eritrea, ex-refinery and retail prices of petroleum products, summary of developments in the labor market, structure of private sector wages, summary of government operations, distribution of net foreign assets, balance of payments, and other related economic indices.